(untitled) (American Journal of Research in Humanities and Social Sciences, 2026)
This article analyzes the state of rural healthcare institutions in the Surkhandarya region between 1940 and 1960, focusing on their material-technical base and staffing levels. It demonstrates that due to the extensive development of the healthcare system during the Soviet era – prioritizing quantitative indicators over qualitative ones – most medical facilities in the region were housed in adapted buildings and lacked modern medical equipment. Furthermore, the study highlights that physicians with higher education worked primarily in urban and district centers, while the rural population was largely served by secondary medical personnel, resulting in a low quality of care.